FOVEAL MÜLLER CELL CONE AS A PROGNOSTIC OPTICAL COHERENCE TOMOGRAPHY BIOMARKER FOR INITIAL RESPONSE TO ANTIVASCULAR ENDOTHELIAL GROWTH FACTOR TREATMENT IN CYSTOID DIABETIC MACULAR EDEMA. Issue 1 (January 2022) - Choi, Mihyun; Yun, Cheolmin; Oh, Jong-Hyun; Kim, Seong-Woo
Abstract : Purpose: To investigate the effect of the foveal Müller cell cone structure on the anatomical and functional response to intravitreal bevacizumab treatment in patients with diabetic macular edema. Methods: In 93 treatment-naive eyes with center-involved cystic type diabetic macular edema, spectral-domain optical coherence tomography scans of baseline were retrospectively evaluated to determine the foveal Müller cell cone structure and prognostic features including length of disorganization in the retinal inner layers and ellipsoid zone disruption. The area and circularity of the foveal avascular zone of the superficial and deep capillary plexus 1 month after intravitreal bevacizumab treatment were evaluated using optical coherence tomography angiography. Results: Destruction of the foveal Müller cell cone structure and a large foveal avascular zone in the deep capillary plexus (mm 2 ) correlated strongly with a poor anatomical response (CST > 250 µ m) at 1 month after first intravitreal bevacizumab (Exp [B] = 29.444, P = 0.002 and Exp [B] = 12.419, P = 0.013, respectively). A destroyed Müller cell cone structure ( P = 0.008) and length of ellipsoid zone disruption ( P < 0.001) at baseline were associated with poor visual acuity at 1 month after the first intravitreal bevacizumab. Conclusion: The foveal Müller cell cone structure correlates with the response to initial antivascular endothelial growth factor treatment. Abstract : Supplemental Digital Content is Available in the Text. This study analyzed the role of the foveal Müller cell cone in the response of cystoid diabetic macular edema to intravitreal bevacizumab (IVB) treatment. The authors noted that a destroyed foveal Müller cell cone structure in cystoid diabetic macular edema was associated with a poor response to initial intravitreal bevacizumab and poor visual acuity.